A low-warpage low-dielectric PBT composite material and preparation method thereof

By adding a specific proportion of PET, olefin copolymer, toughener, glass fiber and silicon micropowder to the PBT composite material, and using the processing methods of high mixer and twin screw extruder, low-warming and low-dielectric PBT composite materials are prepared, which solves the problem that low-dielectric and low-warping cannot be used in the existing technology, and achieves the dielectric performance and structural performance suitable for electronic equipment in the 5G era.

CN116200009BActive Publication Date: 2025-03-14SHANGHAI SUNNY NEW TECH DEV CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211678942.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-26
Publication Date
2025-03-14
Estimated Expiration
2042-12-26

AI Technical Summary

Technical Problem

The prior art cannot have both medium and low dielectric and low warpage, and it is difficult to meet the requirements of high-speed data transmission in high-frequency environments in electronic devices in the 5G era.

Method used

A low warpage low dielectric PBT composite material is used, which includes a thermoplastic polyester resin composition in a specific proportion, an olefin copolymer, a toughener, glass fibers and silicon micropowders. The processing temperature and screw speed are controlled by high mixer mixing and twin-screw extruder processing to prepare composite materials with excellent dielectric properties and low warpage characteristics.

Benefits of technology

It realizes the warping performance of composite materials while maintaining low dielectric constant and dielectric loss, and is suitable for electronic devices in the 5G era, especially large components such as base station shells.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a low-warpage low-dielectric PBT composite material and a preparation method thereof, product: by weight, including 20-62 parts of thermoplastic polyester resin composition, 1-10 parts of olefin copolymer, 1-10 parts of toughening agent, 15-35 parts of glass fiber and 10-30 parts of silicon powder; the thermoplastic polyester resin composition includes PBT and PET, the weight portion of PBT in the thermoplastic polyester resin composition is greater than 70%, and the weight portion of PET in the thermoplastic polyester resin composition is not less than 9.5%; method: the raw materials other than glass fiber are mixed to obtain a mixture, the mixture is fed into a twin-screw extruder from the main feed port, and the glass fiber is fed into the twin-screw extruder from the side feed port at the same time, the processing temperature of the twin-screw extruder is controlled to be 220-260°C, and extrusion granulation is performed to obtain the product. The method of the present invention is simple, and the product of the present invention has both excellent low warpage and low dielectric properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials and relates to a low-warpage and low-dielectric PBT composite material and a preparation method thereof. Background Art

[0002] With the advent of the 5G era, electronic products have increasingly higher requirements for high-speed data transmission in high-frequency environments, and have more stringent requirements on the electromagnetic delay rate and loss of electronic equipment than 4G. Low delay and low loss most typically require materials to have relatively low dielectric constants and dielectric losses.

[0003] PBT material has low water absorption, good fluidity, and stable dimensions. It is one of the most commonly used materials in the 5G communication field. Unmodified PBT material has insufficient strength and temperature resistance, which limits its application in structural parts. It is usually necessary to enhance and modify it. The factors affecting the dielectric properties of polymer materials mainly include two aspects. One is the polarization ability of the resin molecules themselves, and the other is the metal ions in the mineral reinforcement materials. In the prior art, the general practice is to add fillers with low dielectric constants to the resin matrix to reduce the influence of the dielectric properties of the material. The dielectric constant of the general mineral reinforcement material has a relatively obvious decrease, but it has little effect on the dielectric loss and is relatively expensive.

[0004] Chinese invention patent CN109679304B discloses a low dielectric glass fiber reinforced PBT composite material and a preparation method thereof, wherein the low dielectric glass fiber reinforced PBT composite material comprises PBT resin, polytetrafluoroethylene powder, filler, end-capping agent, low dielectric glass fiber, antioxidant, and lubricant. The low dielectric glass fiber reinforced PBT composite material of the invention effectively reduces the dielectric constant and dielectric loss factor of the PBT composite material while maintaining the strength of the glass fiber reinforced PBT material, and ensures that there are no appearance defects such as floating fibers and the glossiness of the product, and meets the ROHS environmental protection standard. However, the technical solution uses polytetrafluoroethylene powder, which has poor dispersion performance and low polarity, and is not suitable for the requirements of metal embedded injection molding parts. At the same time, low dielectric materials such as polytetrafluoroethylene and low dielectric glass fiber are relatively expensive, which is not conducive to the large-scale use of products. It is also not suitable for large parts such as base station housings due to its warping reasons.

[0005] Therefore, it is of great significance to study a low-warpage and low-dielectric PBT composite material and a preparation method thereof to solve the problem that low dielectric and low warpage cannot be achieved at the same time in the prior art. Summary of the invention

[0006] The purpose of the present invention is to solve the problems existing in the prior art and to provide a low-warpage and low-dielectric PBT composite material and a preparation method thereof.

[0007] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0008] A low-warpage low-dielectric PBT composite material, comprising, by weight, 20-62 parts (preferably 39-62 parts) of a thermoplastic polyester resin composition, 1-10 parts (preferably 3-7 parts) of an olefin copolymer, 1-10 parts (preferably 4-8 parts) of a toughening agent, 15-35 parts (preferably 15-25 parts) of glass fiber (the glass fiber used in the present invention is a conventional glass fiber with a dielectric constant of 6.5-7 (1 GHZ)) and 10-30 parts (preferably 15-25 parts) of silicon powder;

[0009] The thermoplastic polyester resin composition comprises PBT (polybutylene terephthalate) and PET (polyethylene terephthalate), the weight proportion of PBT in the thermoplastic polyester resin composition is greater than 70%, the weight proportion of PET in the thermoplastic polyester resin composition is not less than 9.5%, the terminal carboxyl content of PBT is 30-40 meq / kg, the terminal carboxyl content is too low, the active functional groups are insufficient, and the subsequent reaction is insufficient, and the terminal carboxyl content is too high, the molecular chain color is unstable, and it is easy to hydrolyze due to high temperature aging;

[0010] The olefin copolymer is ethylene-maleic anhydride copolymer;

[0011] The silicon micropowder is silicon micropowder surface-treated with aminosilane, and its particle size D50 is 1-5 μm and D90 is 3-10 μm.

[0012] The hydroxyl content in PBT has a direct negative impact on the dielectric constant. If the hydroxyl content is too high, the dielectric constant will increase in the later water absorption. The present invention uses a PBT resin with a high carboxyl content as a base material. On the one hand, the hydroxyl in the system can be neutralized, thereby reducing the dielectric constant. At the same time, a specific proportion of PET is added in the scheme, and its crystallization performance is relatively poor. When the parts are injection molded, it is relatively "slow to cool". Large thin-walled parts can be injection molded at low temperature and low speed, and the content of amorphous molecular chains in the system is increased to form more "gaps" to accommodate more mineral fillers. Not only does it have excellent surface quality, but it also strengthens the orderly dispersion of fillers in the polymer resin to form a skeleton structure that can limit the vibration of the polymer chain under a high-frequency electromagnetic field, thereby reducing dielectric loss. On the other hand, the incompletely reacted carboxyl functional groups can be used to react with metal treatment liquids in nano injection molding to improve peel strength and expand the application in nano injection molding.

[0013] As the preferred technical solution:

[0014] As described above, a low-warpage low-dielectric PBT composite material has a tensile strength of 90-120 MPa and a notched impact strength of 10-16 KJ / m 2, the vertical shrinkage rate is 0.14~0.24%, the vertical shrinkage rate is 0.19~0.29%, the dielectric constant is 3.1-3.4, and the dielectric loss is 0.006~0.009.

[0015] As described above, the low-warpage and low-dielectric PBT composite material has a melting point of 215-230° C. as measured by the DSC test method, a terminal carboxyl content of 20-50 meq / kg, and preferably a terminal carboxyl content of 30-40 meq / kg.

[0016] In the low-warpage and low-dielectric PBT composite material as described above, the melting point of PET measured by the DSC test method is 245-265° C., and the weight proportion of PET in the thermoplastic polyester resin composition is no more than 20%.

[0017] In the low-warpage and low-dielectric PBT composite material as described above, the olefin copolymer is a high-density ethylene-maleic anhydride copolymer, and the grafting rate is 0.5%-1%.

[0018] In the low-warpage and low-dielectric PBT composite material as described above, the toughening agent is an ethylene-methyl acrylate-GMA terpolymer, wherein the mass content of GMA is 5-10%.

[0019] In the low-warpage and low-dielectric PBT composite material as described above, the glass fiber is alkali-free glass fiber.

[0020] In the low-warpage and low-dielectric PBT composite material as described above, the silicon powder is high-purity SiO2 powder, wherein the SiO2 component content is greater than 99.5wt%, and preferably the SiO2 component content is greater than 99.8wt%.

[0021] The present invention also provides a method for preparing a low-warpage and low-dielectric PBT composite material as described in any of the above items, wherein raw materials other than glass fiber are placed in a high-speed mixer and mixed for 3-5 minutes and then discharged to obtain a mixture, the mixture is fed into a twin-screw extruder from a main feeding port, and the glass fiber is fed into the twin-screw extruder from a side feeding port at the same time, the processing temperature of the twin-screw extruder is controlled at 220-260°C, and extrusion granulation is performed to obtain a low-warpage and low-dielectric PBT composite material.

[0022] As the preferred technical solution:

[0023] In the preparation method as described above, the screw speed of the twin-screw extruder is 180-600 rpm.

[0024] Beneficial Effects

[0025] (1) In a low-warpage, low-dielectric PBT composite material of the present invention, an ethylene-maleic anhydride graft having good dielectric properties is added. On the one hand, it can react with the surface groups of the filler (glass fiber and silica powder) and PBT, so that the PBT and the filler are more closely combined, playing the role of a binder and improving the surface performance; on the other hand, it has a low melting point and mainly forms a dense PE layer on the surface of the PBT, which can isolate the erosion of water vapor, prevent the hydrolysis of the PBT, and avoid performance degradation and color instability; in addition, the synergistic effect of the ethylene-maleic anhydride graft and ethylene-methyl acrylate-GMA can be more closely combined with the filler surface, so that the filler has better dispersibility. Controlling the content of GMA can obtain a higher toughening efficiency, thereby reducing the influence of the toughening agent on the dielectric loss.

[0026] (2) In a method for preparing a low-warpage and low-dielectric PBT composite material of the present invention, silicon micropowder and glass fiber are mixed and compounded in a certain proportion so that the composite material has the characteristic of low warpage; wherein, silicon micropowder has an extremely low metal impurity content, the raw material is easy to obtain, the price is economical, and the dielectric properties itself are relatively excellent. Conventional glass fiber reinforced materials can be used to meet the low dielectric requirements. By controlling the particle size of silicon micropowder and treating its surface, it can be effectively dispersed in the gaps between the molecular chains of the glass fiber skeleton, limiting the mobility of the resin molecular chains and reducing the dielectric loss. At the same time, its own anisotropy and the difference in the lateral and longitudinal shrinkage rates are relatively small. DETAILED DESCRIPTION

[0027] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0028] The detection methods of the relevant properties of the PBT composite materials prepared in the embodiments and comparative examples are as follows:

[0029] The tensile strength test method is: test according to ISO 527;

[0030] The notched impact strength test method is: Test according to ISO 179;

[0031] The test method for vertical shrinkage and horizontal shrinkage is: Test according to ISO 294; the lower the difference between vertical shrinkage and horizontal shrinkage, the better the low warpage performance;

[0032] The test method for dielectric constant and dielectric loss is: test in accordance with IEC 60250 (5GHZ).

[0033] Example 1

[0034] A method for low-warpage low-dielectric PBT composite material, the specific steps are as follows:

[0035] (1) Prepare raw materials:

[0036] Prepare 42 parts of PBT (Changchun PBT 1100-X, Taiwan, China), 8 parts of PET (Shanghai Yuanfang PETCB-608S), 4 parts of olefin copolymer (Jia Yirong CMG9904), 4 parts of toughening agent (DuPont 4170), 25 parts of glass fiber (GF534A from Jushi Group) and 15 parts of silica powder (L10 from Suzhou Jinyi New Materials);

[0037] (2) Preparation of low warpage and low dielectric PBT composite materials:

[0038] The raw materials except glass fiber are placed in a high-speed mixer and mixed for 3 to 5 minutes before discharging to obtain a mixture. The mixture is fed into a twin-screw extruder from a main feeding port, and the glass fiber is fed into the twin-screw extruder from a side feeding port. The processing temperature of the twin-screw extruder is controlled at 220 to 260°C, the screw speed is 180 to 600 rpm, and extrusion granulation is performed to obtain a low-warpage and low-dielectric PBT composite material.

[0039] The final low-warpage, low-dielectric PBT composite material has a tensile strength of 96MPa and a notched impact strength of 12KJ / m 2 , the vertical shrinkage rate is 0.18%, the horizontal shrinkage rate is 0.24%, the dielectric constant is 3.22, and the dielectric loss is 0.0084.

[0040] Comparative Example 1

[0041] A method for preparing a PBT composite material is basically the same as that of Example 1, except that PBT with a low terminal carboxyl content (Yizheng Chemical Fiber, brand PBT GX111) is used in this comparative example to replace the PBT (Changchun PBT1100-X from Taiwan, China) in the original Example 1.

[0042] The final PBT composite material has a tensile strength of 92MPa and a notched impact strength of 10.2KJ / m 2 , the vertical shrinkage is 0.19%, the horizontal shrinkage is 0.26%, the dielectric constant is 3.21, and the dielectric loss is 0.0098.

[0043] Comparative Example 2

[0044] A method for preparing a PBT composite material is basically the same as that of Example 1, except that in this comparative example, the proportion of the olefin copolymer is 0 and the proportion of the PBT resin is 46.

[0045] The final PBT composite material has a tensile strength of 94MPa and a notched impact strength of 9.8KJ / m 2 , the vertical shrinkage is 0.20%, the horizontal shrinkage is 0.27%, the dielectric constant is 3.27, and the dielectric loss is 0.0094.

[0046] Comparative Example 3

[0047] A method for preparing a PBT composite material is basically the same as that of Example 1, except that the glass fiber in Example 1 is replaced by the silicon powder in Example 1 of the same mass in this comparative example.

[0048] The final PBT composite material has a tensile strength of 57MPa and a notched impact strength of 12KJ / m 2 , the vertical shrinkage rate is 0.91%, the horizontal shrinkage rate is 1.03%, the dielectric constant is 3.11, and the dielectric loss is 0.0064.

[0049] Comparative Example 4

[0050] A method for preparing a PBT composite material is basically the same as that of Example 1, except that the glass fiber of Example 1 of equal mass is used in this comparative example to replace the silicon powder in the original Example 1.

[0051] The final PBT composite material has a tensile strength of 140MPa and a notched impact strength of 16KJ / m 2 , the vertical shrinkage rate is 0.13%, the horizontal shrinkage rate is 0.57%, the dielectric constant is 3.79, and the dielectric loss is 0.0091.

[0052] Example 2

[0053] A method for low-warpage low-dielectric PBT composite material, the specific steps are as follows:

[0054] (1) Prepare raw materials:

[0055] Prepare 42 parts of PBT (Changchun PBT 1100-X, Taiwan, China), 8 parts of PET (Shanghai Yuanfang PETCB-608S), 4 parts of olefin copolymer (Jia Yirong CMG9904), 6 parts of toughening agent (DuPont 4170), 15 parts of glass fiber (GF534A from Jushi Group) and 25 parts of silica powder (L10 from Suzhou Jinyi New Materials);

[0056] (2) Preparation of low warpage and low dielectric PBT composite materials:

[0057] The raw materials except glass fiber are placed in a high-speed mixer and mixed for 3 to 5 minutes before discharging to obtain a mixture. The mixture is fed into a twin-screw extruder from a main feeding port, and the glass fiber is fed into the twin-screw extruder from a side feeding port. The processing temperature of the twin-screw extruder is controlled at 220 to 260°C, the screw speed is 180 to 600 rpm, and extrusion granulation is performed to obtain a low-warpage and low-dielectric PBT composite material.

[0058] The final low-warpage, low-dielectric PBT composite material has a tensile strength of 90MPa and a notched impact strength of 10KJ / m 2 , the vertical shrinkage rate is 0.24%, the horizontal shrinkage rate is 0.29%, the dielectric constant is 3.17, and the dielectric loss is 0.0075.

[0059] Example 3

[0060] A method for low-warpage low-dielectric PBT composite material, the specific steps are as follows:

[0061] (1) Prepare raw materials:

[0062] Prepare 56 parts of PBT (Changchun PBT 1100-X, Taiwan, China), 6 parts of PET (Shanghai Yuanfang PETCB-608S), 3 parts of olefin copolymer (Jia Yirong CMG9904), 5 parts of toughening agent (DuPont 4170), 20 parts of glass fiber (GF534A from Jushi Group) and 20 parts of silica powder (L10 from Suzhou Jinyi New Materials);

[0063] (2) Preparation of low warpage and low dielectric PBT composite materials:

[0064] The raw materials except glass fiber are placed in a high-speed mixer and mixed for 3 to 5 minutes before discharging to obtain a mixture. The mixture is fed into a twin-screw extruder from a main feeding port, and the glass fiber is fed into the twin-screw extruder from a side feeding port. The processing temperature of the twin-screw extruder is controlled at 220 to 260°C, the screw speed is 180 to 600 rpm, and extrusion granulation is performed to obtain a low-warpage and low-dielectric PBT composite material.

[0065] The final low-warpage, low-dielectric PBT composite material has a tensile strength of 105MPa and a notched impact strength of 15KJ / m 2 , the vertical shrinkage rate is 0.2%, the horizontal shrinkage rate is 0.25%, the dielectric constant is 3.27, and the dielectric loss is 0.0068.

[0066] Example 4

[0067] A method for low-warpage low-dielectric PBT composite material, the specific steps are as follows:

[0068] (1) Prepare raw materials:

[0069] Prepare 38 parts of PBT (Changchun PBT 1100-X, Taiwan, China), 7 parts of PET (Shanghai Yuanfang PETCB-608S), 7 parts of olefin copolymer (Jia Yirong CMG9904), 8 parts of toughening agent (DuPont 4170), 20 parts of glass fiber (GF534A from Jushi Group) and 20 parts of silica powder (L10 from Suzhou Jinyi New Materials);

[0070] (2) Preparation of low warpage and low dielectric PBT composite materials:

[0071] The raw materials except glass fiber are placed in a high-speed mixer and mixed for 3 to 5 minutes before discharging to obtain a mixture. The mixture is fed into a twin-screw extruder from a main feeding port, and the glass fiber is fed into the twin-screw extruder from a side feeding port. The processing temperature of the twin-screw extruder is controlled at 220 to 260°C, the screw speed is 180 to 600 rpm, and extrusion granulation is performed to obtain a low-warpage and low-dielectric PBT composite material.

[0072] The final low-warpage, low-dielectric PBT composite material has a tensile strength of 98MPa and a notched impact strength of 16KJ / m 2 , the vertical shrinkage rate is 0.22%, the horizontal shrinkage rate is 0.27%, the dielectric constant is 3.31, and the dielectric loss is 0.0081.

[0073] Example 5

[0074] A method for low-warpage low-dielectric PBT composite material, the specific steps are as follows:

[0075] (1) Prepare raw materials:

[0076] Prepare 33 parts of PBT (Changchun PBT 1100-X, Taiwan, China), 6 parts of PET (Shanghai Yuanfang PETCB-608S), 5 parts of olefin copolymer (Jia Yirong CMG9904), 6 parts of toughening agent (DuPont 4170), 25 parts of glass fiber (GF534A from Jushi Group) and 25 parts of silica powder (L10 from Suzhou Jinyi New Materials);

[0077] (2) Preparation of low warpage and low dielectric PBT composite materials:

[0078] The raw materials except glass fiber are placed in a high-speed mixer and mixed for 3 to 5 minutes before discharging to obtain a mixture. The mixture is fed into a twin-screw extruder from a main feeding port, and the glass fiber is fed into the twin-screw extruder from a side feeding port. The processing temperature of the twin-screw extruder is controlled at 220 to 260°C, the screw speed is 180 to 600 rpm, and extrusion granulation is performed to obtain a low-warpage and low-dielectric PBT composite material.

[0079] The final low-warpage, low-dielectric PBT composite material has a tensile strength of 112MPa and a notched impact strength of 14KJ / m 2 , the vertical shrinkage rate is 0.14%, the horizontal shrinkage rate is 0.19%, the dielectric constant is 3.37, and the dielectric loss is 0.0089.

[0080] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for a person skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to perform equivalent replacements on some of the technical features thereof. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention. Several improvements and supplements may be made without departing from the method of the present invention, and these improvements and supplements shall also be regarded as the protection scope of the present invention.

Claims

1. A low-warpage, low-dielectric PBT composite material, characterized in that: The invention comprises, by weight, 20-62 parts of a thermoplastic polyester resin composition, 1-10 parts of an olefin copolymer, 1-10 parts of a toughening agent, 15-35 parts of glass fibers and 10-30 parts of silicon powder; The thermoplastic polyester resin composition comprises PBT and PET, wherein the weight proportion of PBT in the thermoplastic polyester resin composition is greater than 70%, the weight proportion of PET in the thermoplastic polyester resin composition is not less than 9.5%, and the terminal carboxyl content of PBT is 30-40 meq / kg; The olefin copolymer is ethylene-maleic anhydride copolymer; The toughening agent is ethylene-methyl acrylate-GMA terpolymer, wherein the mass content of GMA is 5-10%; The silicon micropowder is silicon micropowder surface-treated with aminosilane, and its particle size D50 is 1-5 μm and D90 is 3-10 μm.

2. The low-warpage, low-dielectric PBT composite material according to claim 1, characterized in that: The melting point of PET measured by the DSC test method is 245-265° C., and the weight proportion of PET in the thermoplastic polyester resin composition is no more than 20%.

3. The low-warpage low-dielectric PBT composite material according to claim 1, characterized in that: The olefin copolymer is a high-density ethylene-maleic anhydride copolymer, and the grafting rate is 0.5%-1%.

4. The low-warpage low-dielectric PBT composite material according to claim 1, characterized in that: The glass fiber is alkali-free glass fiber.

5. The low-warpage, low-dielectric PBT composite material according to claim 1, characterized in that: Silica powder is high-purity SiO2 powder, in which the SiO2 component content is greater than 99.5wt%.

6. A method for preparing a low-warpage low-dielectric PBT composite material according to any one of claims 1 to 5, characterized in that: The raw materials except glass fiber are mixed to obtain a mixture, and the mixture is fed into a twin-screw extruder from a main feeding port. At the same time, the glass fiber is fed into the twin-screw extruder from a side feeding port. The processing temperature of the twin-screw extruder is controlled at 220-260° C., and extrusion granulation is performed to obtain a low-warpage and low-dielectric PBT composite material.

7. The preparation method according to claim 6, characterized in that: The screw speed of the twin-screw extruder is 180-600 rpm.

Citation Information

Patent Citations

  • A PBT / PCT composite material, its preparation method and applications

    CN109679304B

  • High rigidity and low warpage polyester composite material and preparation method thereof

    CN107383797A

  • Low-warpage halogen-free expanded flame-retardant long glass fiber reinforced polypropylene composite material and preparation method thereof

    CN108250566A